(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Information security is a significant cause for concern, mainly because of the explosive growth in internet usage over the last few years. Due to this growth, there have been occurrences of unauthorized access, which have been reduced thanks to “using a range of secure communication protocols, such as encryption and data concealment”. Using DNA’s bio-molecular capabilities, the usage of DNA as a carrier for encryption and data concealing has increased in recent years. The realization that DNA may function as a transport medium sparked this movement. In this study, we first examine and briefly outline the evolution of the present DNA coding system. After that, the several ways DNA has been used to enhance encryption techniques are categorized. The benefits and drawbacks of these algorithms and the most recent advancements in DNA-based encryption techniques are discussed. Finally, we provide our thoughts on the potential future of DNA-based encryption algorithms.